THE EFFECTS OF IRON DEFICIENCY ON THE HEPATOCYTE: A BIOCHEMICAL AND ULTRASTRUCTURAL STUDY - Dallman, Peter R. (The Rockefeller University Press, 1971)
Effects of iron deficiency on the hepatocyte were studied quantitatively in the rat by combining ultrastructural and biochemical techniques. After 3–8 wk of an iron-deficient diet, the percentage of cytoplasm occupied by mitochondria increased progressively compared with complete diet values. The increment resulted primarily from an enlargement of individual mitochondria rather than from an increased mitochondrial number. Many mitochondria were completely divided by a double membrane, often at a point of constriction. After 2 days of iron administration, mitochondria were of heterogeneous size, shape, and electron opacity. After 5 days, essentially all mitochondria had become normal in configuration. The rate of reversal of the morphological abnormality was more rapid than would be anticipated if it coincided with known rates of renewal of mitochondrial DNA or protein. The concentrations of mitochondrial cytochromes were more rapidly depressed as a result of iron deprivation than those of microsomal cytochromes. Cytochromes c and a were decreased after 3 and 8 wk of exposure to the deficient regimen. Cytochrome P 450 was not decreased after a 3 wk exposure to the deficient diet and responded normally to phenobarbital treatment with a fourfold increase in total hepatic content; its concentration was depressed only after 8 wk of exposure to the deficient diet. There was no reduction in cytochrome b (5) concentration.